Nurturing students entrepreneurial spirit through digital communication and entrepreneurship training at SD IT Al Fazhira [Menumbuhkan jiwa wirausaha siswa melalui pelatihan komunikasi digital dan kewirausahaan di SD IT Al Fazhira] - Rismawati; Mawaddah; Ulfa Erfendy; Blangi Intan Maharani (Buletin Pengabdian Bulletin of Community Services, 2025)
Entrepreneurship education needs to be instilled from an early age to form a generation that is independent, creative, and ready to face the challenges of the digital era. Therefore, it is necessary to conduct communication and entrepreneurship training at SD IT Al Fazhira with the aim of fostering students' entrepreneurial spirit through an interactive and practical approach. The methods used include lectures, educational videos, discussions, and simulations of entrepreneurial activities by utilizing digital media. The results of the activity showed that students were very enthusiastic and able to understand the concept of entrepreneurship and the application of digital communication in simple businesses. Simulation activities show students' ability to apply the material through the utilization of digital platforms such as social media and e-commerce. In conclusion, this training is effective in improving students' digital literacy and entrepreneurial spirit from an early age, while equipping them with relevant life skills in the future.